Koroner arter hastalığı ve iş yaşamı - OĞUZ, SIDIKA; ÇAMCI, GÜLŞAH (My University, 2016)
Koroner arter hastalığı olan bireylerin; iş tanımı, işyerinden aldığı destek, işyerindeki çalışma protokolleri, çalışma saatleri ve iş seyahatleri gibi nedenler hastalık yönetiminde güçlükler yaratabilir. Çalışmalarda, vardiyalı çalışmanın, iş stresinin, fazla veya az iş saatlerinin kardiyovasküler hastalık riskini artırdığı bulunmuştur. Bu nedenle her bireyin düşük sosyoekonomik düzey, sosyal destek eksikliği, iş stresi, aile yaşamında depresyon, anksiyete, düşmanlık ve D tipi kişilik gibi psikososyal faktörlerin içinde olduğu psikososyal strese karşı sağlıklı davranışlar edinmesi koroner arter hastalığı riskini azaltabilir. Hemşireler, koroner arter hastalığı olan bireylere geniş kapsamlı kardiyak rehabilitasyon eğitimi vererek, bireylerin iş stresiyle daha iyi baş etmesini ve iş yaşamına adaptasyonunu sağlayabilir. Ayrıca yönetici veya iş sahibinin çalışanını iş stresinin azaltılması, çalışma saatlerinin düzeltilmesi, olumlu sağlık davranışları ve sosyal destek yönünden desteklemesi önemlidir.

Individuals with coronary artery disease may be created difficulties in disease management for reasons such as job description, support from the workplace, study protocols in the workplace, working hours and business trips. In studies; shift work, occupational stres, much or little work hours has been found increasing the risk of cardiovascular disease. Therefore; every individual can reduce the risk of coronary artery disease after acquisition of healthy behaviors against the psychosocial stress as well as in psychosocial factors such as low socio-economic status, lack of social support, occupational stress, depression in family life, anxiety, hostility and D type personality. When nurses provide trainning for comprehensive cardiac rehabilitation to individuals with coronary artery disease, individuals can be coped with occupational stress better and lead to adaptation of work life. In addition, it is important that business owners or managers must support to employees in terms of the reduction of occupational stres, correction of working hours, positive health behaviors and social support.
Coronary artery disease and occupational life
Keywords: Koroner arter hastalığı; iş yeri; stres; Coronary artery disease; workplace; dtress